PERENCANAAN STRUKTUR ATAS DAN RENCANA ANGGARAN BIAYA PADA PEMBANGUNAN KELURAHAN CICAHEUM - Andrea, Sara Ivanna; Prasetyo, Denny Adi (Jurnal Mahasiswa Terapan; Vol 1 No 1 (2024): Jurnal Mahasiswa Terapan, 2024)
The rapid development of Bandung in economic, social, and tourism sectors has led to urbanization from surrounding areas. Kiaracondong District, particularly Cicaheum Village, has become one of the most densely populated areas in Bandung. To address this growth, the Cicaheum Village Office will be reconstructed from a single-story to a three-story building. This project requires careful structural planning to ensure strength and load-bearing capacity while optimizing costs and resources through RAB analysis.  This research aims to analyze the structure and RAB of the office's upper structure using initial structural design and a quantitative approach. Numerical calculations and structural analysis were conducted using SAP2000 and Microsoft Excel 2016.  The results are as follows: a) columns of 350x350 mm with reinforcement 4D25 and D16-250, b) beam B1 of 300x400 mm with reinforcement 3D20 and 2D20 with shear reinforcement 2D16-170, c) beam B2 of 200x300 mm with reinforcement 3D14 and 2D14 with shear reinforcement 2D12-120, d) floor plate with 120 mm thickness, with varied reinforcement configurations. The RAB for the upper structure of the Cicaheum Village Office is IDR 778,746,000.